Polycation-induced assembly of purified tubulin. - Erickson, H P (1976)
Several different polycations have been found that can substitute for the microtubule-associated proteins, or tau factor, in facilitating assembly of tubulin that has been purified by ion exchange chromatography. In low concentrations of the polycation diethylaminoethyl-dextran, 7 mg of tubulin is pelleted per 1 mg of polycation added. Under conditions favorable to microtubule assembly the entire pellet is seen by electron microscopy to consist of "double wall microtubules", which are essentially identical to normal microtubules in subunit structure and arrangement. When assembly is inhibited approximately the same amount of tubulin is pelleted, but it is in the form of clusters of curved sheets or filaments apparently related to tubulin rings. When conditions are changed to favor assembly, the tubulin within these clusters appears to reassemble to form the double wall microtubules.